O Incidente de Resolução de Demandas Repetitivas como alternativa para a redução da litigiosidade envolvendo as Fazendas Públicas Estaduais - Maia, Heloise Wittmann (2020)
This study aims to analyze the Repetitive Demand Resolution Incident (RDRI) as an alternative to the drafting of litigation involving the State Public Treasuries After all, the State Government presents itself as one of the largest litigants of the judiciary. Therefore, the focus of the present work is to understand the precedent system created by the Civil Procedure Code of 2015, as well as the referred Incident with the objective of checking, based on such concepts, how its application would help reduce the litigation involving the State Public Power. This may allow its more rational and efficient pratice and will consequently meet the public interest that seeks this response by the State